Prevalence of Iron Deficiency Anemia among Infants Consuming Cow’s Milk : Prevalence of Iron Deficiency Anemia - Bai, Anila; Shaikh, Farzana; Kumar, Suresh; Ahmed, Ayesha; Marium, .; Shaikh, Muhammad Akram (Pakistan Journal of Health Sciences, 2023)
Iron Deficiency Anemia (IDA) in children is a public health issue affecting child morbidity, mortality, and cognitive development. Infants fed cow’s milk are at a higher risk of severe IDA due to calcium and iron absorption competition. Objective: To determine the frequency of Iron deficiency anemia among Cow Milk Fed Infants. Methods: This cross-sectional study was conducted at Peadiatric wards of Liaquat University Hospital Hyderabad and Jamshoro from November 2020 to April 2021. All the full-term infants with age of up to 6 months either gender and having history of cow’s milk consumption and clinically diagnosed to have anemia were included. Infants had 3ml intravenous blood samples taken to get a complete blood picture and ferritin level. All the mothers were interviewed regarding duration of cow’s milk consumption. Data were collected via a predesigned proforma. Results: Total 323 infants were studied to assess the frequency of iron deficiency anemia among cow’s milk infants up to 6 months and the mean age of infants was 4.11 ± 1.31 months. Females were 56.3% and males were 43.7%. Overall average of hemoglobin was 8.92 ± 1.09 g/dl, and overall mean of ferritin level was 90.16 ± 17.71 ng/ml. Frequency of iron deficiency anemia was found to be 18.6%. Conclusions: As per study conclusion overall frequency of iron deficiency anemia was observed to be 18.6% and cow’s milk consumption has been observed as a risk factor of infant’s anemia.